Modeling increased riverine nitrogen export: Source tracking and integrated watershed-coast management. Issue 2 (30th December 2015) - Yu, Dan; Yan, Weijin; Chen, Nengwang; Peng, Benrong; Hong, Huasheng; Zhuo, Guihua
Abstract: The global NEWS model was calibrated and then used to quantify the long term trend of dissolved inorganic nitrogen (DIN) export from two tributaries of Jiulong River (SE China). Anthropogenic N inputs contributed 61–92% of river DIN yield which increased from 337 in 1980s to 1662 kg N km − 2  yr − 1 in 2000s for the North River, and from 653 to 3097 kg N km − 2  yr − 1 for the West River. North River and West River contributed 55% and 45% respectively of DIN loading to the estuary. Rapid development and poor management driven by national policies were responsible for increasing riverine N export. Scenario analysis and source tracking suggest that reductions of anthropogenic N inputs of at least 30% in the North River (emphasis on fertilizer and manure) and 50% in the West River (emphasis on fertilizer) could significantly improve water quality and mitigate eutrophication in both river and coastal waters. Highlights: Modeling increased DIN export and identifying source contribution by tributary. Anthropogenic N inputs contributed 61%–92% of total DIN yield in 1980–2010. Rapid development and poor management were responsible for increasing DIN export. At least 30% (North River) and 50% (West River) reductions of N inputs are suggested. Current study highlights an integrated watershed-coast management of nutrient.